ASSOCIATION OF ANTI-DOUBLE STRANDED DNA ANTIBODIES, C-REACTIVE PROTEIN, AND ERYTHROCYTE SEDIMENTATION RATE FROM PATIENTS WITH SYSTEMIC LUPUS ERYTHEMATOSUS IN TAMIL NADU. - Manikandan, Natesan; Rameshkumar, Marimuthu Ragavan; S, Rajeshwari; Arunagirinathan, Narasingam (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: To determine the serum levels of anti-double stranded DNA (anti-dsDNA) antibodies, serum C-reactive protein (CRP), and erythrocyte sedimentation rate (ESR) in patients with systemic lupus erythematosus (SLE) from Tamil Nadu, and elucidate their correlation level. Methods: Blood samples were collected from 100 SLE patients (mean age 39 years) attended to the Rheumatology Care Centre, Rajiv Gandhi Government General Hospital, Chennai. Anti-dsDNA antibodies IgG in SLE patients were analyzed by Enzyme-linked Immunosorbent Assay, and CRP was measured by turbidimetry. ESR was measured by Westergren method. Results: In a total of 100 SLE patients, 72 cases were positive for anti-dsDNA antibody. The mean level of anti-dsDNA antibodies in 72 SLE patients was 102 IU/ml. Among the 100 SLE cases, 92 cases (92%) had elevated levels of CRP and their mean level was 11 ± 4 mg/L. The mean ESR levels were high in SLE patients (56 ± 20 mm/hr). Significant association of anti-dsDNA antibodies with ESR (r = 0.357; p < 0.001) and CRP (r = 0.81; p = 0.023) was found. Conclusion: Anti-dsDNA antibodies had a significant association with CRP and ESR. The result of our study suggests an association of anti-dsDNA antibodies with ESR and CRP and was linked with SLE disease progression.